Baryon Acoustic Oscillations. Equation and physical interpretation - Pardo Calderón, Leandro Manuel (Scientia et Technica, 2018)
Baryon Acoustic Oscillations are a phenomenon occurred before matter-radiation decoupling, characterized because the baryonic matter perturbation presents oscillations, as the name suggests. These perturbations propagate like a pressure wave on the photon-baryon ﬂuid produced by gravitational potentials, which join the baryonic matter, and collisions of baryons and photons, which scatter it. This paper shows the Baryon Acoustic Oscillations equation and it provides its physical meaning. Besides, it presents software CAMB as a tool to ﬁnd BAO equation solutions and support for its physical description.